Advances in Manufacturing II Volume 4 - Mechanical Engineering - Gapiński, Bartosz; Szostak, Marek; Ivanov, Vitalii (Lecture Notes in Mechanical Engineering,, 2019)
This book covers a variety of topics related to machine manufacturing and concerning machine design, product assembly, technological aspects of production, mechatronics and production maintenance. Based on papers presented at the 6th International Scientific-Technical Conference MANUFACTURING 2019, held in Poznan, Poland on May 19-22, 2019, the different chapters reports on cutting-edge issues in constructing machine parts, mechatronic solutions and modern drives. They include new ideas and technologies for machine cutting and precise processing. Chipless technologies, such as founding, plastic forming, non-metal construction materials and composites, and additive techniques alike, are also analyzed and thoroughly discussed. All in all, the book reports on significant scientific contributions in modern manufacturing, offering a timely guide for researchers and professionals developing and/or using mechanical engineering technologies that have become indispensable for modern manufacturing. .